2019
DOI: 10.1038/s41598-019-44915-8
|View full text |Cite
|
Sign up to set email alerts
|

δ-MnO2 nanoflower/graphite cathode for rechargeable aqueous zinc ion batteries

Abstract: Manganese oxide (MnO 2 ) is one of the most promising intercalation cathode materials for zinc ion batteries (ZIBs). Specifically, a layered type delta manganese dioxide (δ-MnO 2 ) allows reversible insertion/extraction of Zn 2+ ions and exhibits high storage capacity of Zn 2+ ions. However, a poor conductivity of δ-MnO 2 , as well as other crystallographic forms, limits its potential applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(107 citation statements)
references
References 46 publications
6
99
0
2
Order By: Relevance
“…However, Kheawhom et al suggest that only Zn 2+ ions insert into δ‐MnO 2 and transform into δ‐ZnMnO 2 in 0.5 m ZnSO 4 electrolyte. [ 15 ] Additionally, Kang et al study the mechanism of Zn 2+ ions intercalation in α‐MnO 2 , the formation of ZnMn 2 O 4 clearly confirms the insertion of Zn 2+ into α‐MnO 2 in 0.5 m Zn(NO 3 ) 2 electrolyte. [ 16 ] There is no doubt that the Zn 2+ ions can be reversibly inserted/extracted in MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Kheawhom et al suggest that only Zn 2+ ions insert into δ‐MnO 2 and transform into δ‐ZnMnO 2 in 0.5 m ZnSO 4 electrolyte. [ 15 ] Additionally, Kang et al study the mechanism of Zn 2+ ions intercalation in α‐MnO 2 , the formation of ZnMn 2 O 4 clearly confirms the insertion of Zn 2+ into α‐MnO 2 in 0.5 m Zn(NO 3 ) 2 electrolyte. [ 16 ] There is no doubt that the Zn 2+ ions can be reversibly inserted/extracted in MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 46–52 ] The reaction mechanisms for these manganese‐based oxides are summarized in Figure 3 . Three main mechanisms are reported for manganese‐based oxide, namely 1) Zn 2+ insertion/extraction, [ 53–55 ] 2) chemical conversion reaction, [ 38 ] and 3) H + /Zn 2+ insertion/extraction. [ 56–58 ]…”
Section: Manganese‐based Oxides and Energy Storage Mechanismsmentioning
confidence: 99%
“…have shown that the incorporation of K into the cathode can also help suppress Mn dissolution . Reducing particle size and increasing surface area of the active material has also been employed to address the poor conductivity of Mn oxides . Furthermore, the reaction mechanism surrounding Mn 3 O 4 materials, and Mn oxide compounds in general, is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1,4,5] Presently, several different categories of materials have been explored for use as cathodes, with the most popular ones being V oxide compounds, [4][5][6][7][8][9][10][11][12][13][14] Prussian blue analogues (PBA), [4,5,[15][16][17][18] and Mn oxide compounds. [4,5,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] To a lesser extent, sustainable quinone analogs, metal sulfides, Chevrel phase compounds, and polyanion based compounds have also been explored. [4,5,36] Of the different materials explored for ZIB cathodes, the most commonly studied material is Mn oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation